(untitled) (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to study the effect of ardu (Ailanthus excelsa) leaf powder feeding on growth performance and economics of feeding in Pantja goats at Goat Unit, Department of Livestock Production Management, G.B. Pant University of Agriculture & Technology, Pantnagar. The study was conducted on a total of sixteen, 6-8 months old kids, which were randomly divided into four groups (T0- Control, T1- 75% Concentrate + 25% ardu leaf powder, T2- 50% Concentrate + 50% ardu leaf powder and T3- 25% Concentrate + 75% ardu leaf powder). Growth parameters were studied by observation of body weight at different time periods viz. 0, 15, 30, 45, 60, 75 and 90 days. The results of the experiment revealed that treatment groups supplemented with ardu leaf powder had significantly (P<0.05) higher body weights than the control group. Maximum body weight during whole experimental period was noted in treatment group supplemented with 75% of ardu leaf powder. All the treatment groups fed with ardu leaf powder showed reduction in feed cost as compared to control with minimum feed cost noted in treatment group fed with 75% of ardu leaf powder.